The effects of direct and indirect written corrective feedback on ESL students’ use of past tenses / Siti Nor Aisyah Ishak - Siti Nor Aisyah, Ishak (2018)
Written corrective feedback (WCF) helps students to distinguish their errors in written work before producing the correct form. In school, WCF is widely used among writing teachers in attempt to improve students’ language accuracy in their written tasks. Experts like Sheen (2007) and Bitchener (2008) believe that WCF plays a significant role in language accuracy development because it is effective and helpful in the development and improvement of students’ accuracy in second language writing. Corrective feedback can be operationalized in terms of direct and indirect. However, in many cases of empirical studies (Ferris, 2003; Chandler, 2006; Bitchener & Knoch, 2009), results were inconclusive because of variation in how the effectiveness of WCF was measured. Hence, the purpose of this study is to investigate the effects of direct and indirect WCF on ESL students’ use of past tenses over a period of 12 weeks. A total of 60 ESL students were put into two treatment groups. Base on a mixed method approach, the study compared the effectiveness of direct WCF and indirect WCF on the accurate use of past tenses measured using pre-post tests, as well as interviewing respondents in order to detect the factors that influence the performance of the students. Findings revealed that the direct group performed slightly better than the indirect group in the post-tests. It was also found that both groups performed statistically significant over time, but there was no significant difference in the learners’ use of past tenses between both groups. The qualitative findings revealed that factors related to leaner attitudes, learner beliefs and the types of scaffolding that took place influence the performance of the students. Both the quantitative and qualitative findings indicate that different types of corrective feedback and the pre-mentioned factors affect students’ achievement in language learning.